Dispersion properties of transversely isotropic layered shells - MARKUŠ, Š; NÁNÁSI, T. (Archives of Acoustics, 1996)
Harmonic wave propagation in thick, cylindrical, three-layered shells of infinite length was studied. Both the outer layers and the core are composites made of short strand fiberglass resin, but the planes of isotropy in the outer layers are orthogonal to the plane of isotropy at the core. A closed form solution of the exact linear equations of elasticity was sought in terms of Frobenius power series. The influence of the core thickness on the dynamics of the wave motion is estimated from numerically computed dispersion curves. Prime consideration was given the asymmetric wave motion and the different types of waves which can occur are identified over a wide range of wave numbers.